The Executive Authority Role in Evaluating the Government Institutions - Majid Jassim, Assist .Prof. Batool (Basra studies journal, 2024)
Evaluating the performance of government institutions is of great importance in demonstrating the level of progress and development in the field of managing the administrative and governmental activities of the country. The executive authority has an important role in evaluating the activity of government institutions by adopting regulatory and supervisory standards related to legal foundations by determining the means and methods of supervision and how these institutions are linked to the administrative and organizational structure of the executive authority. In addition to adopt the foundations related to drawing up the general policy of the state and its national trends in following modern methods of evaluation, by introducing modern development and administrative programs that in turn enhance the activity of institutions and their ability to produce in all fields and its positive repercussions in achieving their set goals and thus achieving the public interest.